Evaluasi Efektivitas Perpindahan Panas Generator Air Cooler pada PT. X - Moch. Gilang Muharam; Alvera Apridalianti Melkias; Indriyani, Indriyani (SURYA TEKNIKA, 2024)
The generator air cooler at PT. X functions as a heat exchanger in the process of cooling air in the generator. As an air cooler for the generator, the generator air cooler must have good effectiveness. Good effectiveness is considered from the heat transfer between the cooling water in the air cooler generator as the cooling medium and the air being circulated, so the heat absorption is expected to be maximized. Based on the calculations conducted, the fin efficiency of the air cooler generator is 41.6%, the overall heat transfer coefficient (U) is 59.49 W/m²°C, the heat transfer rate on the fins is 312.2703 kW, the heat transfer rate on the tubes is 84.39696 kW, the number of transfer units (NTU) is 0.853, and the overall effectiveness of the air cooler generator system is 53.06%, showing a decrease of 33.94% from the maximum effectiveness of 87%.